2020
DOI: 10.21203/rs.3.rs-23243/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic distribution of angle kappa and its biomechanical relationships in population who are suitable for excimer laser refractive surgery

Abstract: Background To explore the dynamic distribution of pupil size and center,the eccentricity distribution of angle kappa, and its correlation with other biomechanics about suitable for excimer laser refractive surgery. Methods Randomly selected 225 patients (407 eyes) who underwent femtosecond laser combined with excimer laser in situkeratomileusis,preoperative use of Wavelight Allegro Topolyzer Corneal Topography ( Wavelight Laser Technologies AG, Erlangen, Germany ) to measure the pupil size and center position,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…Large WTW values correlate with changes in pupillary diameter and can affect angle kappa measurements. (17,19) In the present study, we found that the mean mesopic angle kappa in the group of patients with an AXL of >27.5 mm was larger compared to the mesopic angle kappa in the group of patients with an AXL of <27.5 mm. However, from correlation testing, a statistically non-significant negative association was observed of the photopic and mesopic angle kappa values with AXL.…”
Section: Discussioncontrasting
confidence: 50%
“…Large WTW values correlate with changes in pupillary diameter and can affect angle kappa measurements. (17,19) In the present study, we found that the mean mesopic angle kappa in the group of patients with an AXL of >27.5 mm was larger compared to the mesopic angle kappa in the group of patients with an AXL of <27.5 mm. However, from correlation testing, a statistically non-significant negative association was observed of the photopic and mesopic angle kappa values with AXL.…”
Section: Discussioncontrasting
confidence: 50%